Aspekt komunikacji społecznej w strategiach autoprezentacyjnych - Stańczyk, Piotr (The aspect of a social communication in self-presentation strategies, 2007)
This article presents the problem of a dependence on the self-presentation, the self presentation dilemma, self-presentation tactics, the discourse and the conception of a communication which is based on the idea of the semantics of situations. The example of political self-presentations displays connections among these theoretical narratives.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Nauki Humanistyczne (11); 2007; nr 1188, s. 25-33